2008
DOI: 10.1177/1469044608091150
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure cuffs as a potential fomite for transmission of pathogenic micro- organisms: A prospective study in a university teaching hospital

Abstract: Objective: To investigate the contamination of blood pressure cuffs on medical, surgical, paediatric and intensive care areas in a university teaching hospital. Design: A comprehensive, prospective study quantitatively and qualitatively evaluating the bacterial contamination on blood pressure cuffs of 100 sphygmomanometers in use in ten hospital units from June through to July 2007. Setting: A university teaching hospital with medical, surgical, paediatric and intensive care units. Results: The inner sides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Briefly, with the aid of sterile gloves, an estimated surface area of 100 cm 2 of BP cuff material coming into direct contact with patients' skin during BP measurement was swabbed using a sterile swab stick moistened with physiological saline. Likewise, thermometers were swabbed using swab sticks moistened with physiological saline as described by Baruah et al (2008). Swabs were labelled appropriately and transferred to the Medical Microbiology Laboratory of Ebonyi State University Abakaliki for analysis.…”
Section: Sampling Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, with the aid of sterile gloves, an estimated surface area of 100 cm 2 of BP cuff material coming into direct contact with patients' skin during BP measurement was swabbed using a sterile swab stick moistened with physiological saline. Likewise, thermometers were swabbed using swab sticks moistened with physiological saline as described by Baruah et al (2008). Swabs were labelled appropriately and transferred to the Medical Microbiology Laboratory of Ebonyi State University Abakaliki for analysis.…”
Section: Sampling Techniquementioning
confidence: 99%
“…Most attention to HAI prevention is given to high-risk invasive diagnostic and therapeutic healthcare tools, while the importance of less critical tools tends to be underestimated (Schwegman 2008;Uneke and Ijeoma 2010). Recent studies have reported the potential nosocomial spread of microbial flora by means of non-critical healthcare tools including stethoscopes (Uneke et al 2009;Schroeder et al 2009), ultrasound transducers (Schabrun et al 2006), gloves (Katherason et al 2010), tourniquets (Ormerod et al 2006), physicians' and nurses' pens (Wolfe et al 2009), scissors (Cleal 2006), white coats (Treakle et al 2009; Uneke and Ijeoma 2010), thermometers (Donkers et al 2001) and blood pressure (BP) cuffs (Baruah et al 2008;Davis 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decision to change cuffs arose from a concern about potential transmission of infection between patients while having their BP measured. 3 Documented evidence in the literature, to support or refute the interchanging of cuffs between devices, is lacking, although current CE marking regulations require that BP devices (including cuffs) are formally validated according to recognised protocols. A new UM-101 was purchased and a systematic comparison of the manufacturer-supplied versus replacement cuffs undertaken and the results of this comparison are presented here.…”
Section: Introductionmentioning
confidence: 99%